Optical, Thermal and Carrier Transport Properties of Porous Silicon Layer Determined Using Photoacoustic Spectroscopy - Chan, Kok Sheng (2006)
In this study, porous silicon layers were fabricated on p-type and n-type silicon substrates by electrochemical etching method at five different current densities (i.e. 16.98, 22.64, 28.29, 33.96 and 39.62) mA/cm2. The etching duration was fixed at 20 minutes. In the second series of preparation, the silicon substrates were anodized at six different etching durations (i.e. 20, 25, 30, 35, 40 and 45 minutes) with constant current density of 22.64 mA/cm2. Photoluminescence spectra, measured by fiber optics spectrophotometer show a peak that is blueshifted towards higher energy as the porosity is increased.